Migration and Macroeconomic Performance in New Zealand: Theory and Evidence - Julie Fry (New Zealand Government, The Treasury, 2014)
New Zealand immigration policy settings are based on the assumption that the macroeconomic impacts of immigration may be significantly positive, with at worst small negative effects. However, both large positive and large negative effects are possible. Reviewing the literature, the balance of evidence suggests that while past immigration has, at times, had significant net benefits, over the past couple of decades the positive effects of immigration on per capita growth, productivity, fiscal balance and mitigating population ageing are likely to have been modest. There is also some evidence that immigration, together with other forms of population growth, has exacerbated pressures on New Zealand's insufficiently-responsive housing market. Meeting the infrastructure needs of immigrants in an economy with a quite modest rate of national saving may also have diverted resources from productive tradable activities, with negative macroeconomic impacts. Therefore from a macroeconomic perspective, a least regrets approach suggests that immigration policy should be more closely tailored to the economy's ability to adjust to population increase. At a minimum, this emphasises the importance of improving the economy's ability to respond to population increase. If this cannot be achieved, there may be merit in considering a reduced immigration target as a tool for easing macroeconomic pressures. More work is required to assess the potential net benefits of an increase in immigration as part of a strategy to pursue scale and agglomeration effects through increased population, or whether a decrease in immigration could facilitate lower interest rates, a lower exchange rate, and more balanced growth going forward.
Keywords: F22; J11; J24; J61; O15; 330; macroeconomics; migration; immigration; emigration; labour market; housing market; factor price equalisation; productivity; growth; scale; agglomeration; Einwanderung; Migrationspolitik; Wirkungsanalyse; Neuseeland